Macrophage-Based Approaches for Cancer Immunotherapy - Anderson, Nicholas R.; Minutolo, Nicholas G.; Gill, Saar; Klichinsky, Michael (Cancer research (Chicago, Ill.), 2021)
Adoptive cell therapy with genetically modified T cells has generated exciting outcomes in hematologic malignancies, but its application to solid tumors has proven challenging. This gap has spurred the investigation of alternative immune cells as therapeutics. Macrophages are potent immune effector cells whose functional plasticity leads to antitumor as well as protumor function in different settings, and this plasticity has led to notable efforts to deplete or repolarize tumor-associated macrophages. Alternatively, macrophages could be adoptively transferred after ex vivo genetic modification. In this review, we highlight the role of macrophages in solid tumors, the progress made with macrophage-focused immunotherapeutic modalities, and the emergence of chimeric antigen receptor macrophage cell therapy.